Developing an intelligent user manager system for controlling smart school network resources - Gani, Abdullah; Mouratidis, H.; Abouzakhar, N.S.; Manson, G.A. (2002)
This paper presents an Intelligent User Manager System (UMAS) for controlling access to network resources in a Smart School network. Network resources, especially in a Smart School, are in short supply and relatively expensive to acquire, therefore a control mechanism should be in place so that available resources can be allocated for legitimate usages only. An intelligent mechanism using Fuzzy Logic is deployed for the purpose of knowledge learning in order to process all the user requests accordingly. A decision of granting a network resource request needs to be based on several data sets that represent the current network state, transmission state and users. The system is analysed and designed using the Tropos Methodology. Tropos was chosen because it covers four stages of development. The proposed system was modelled using Fuzzy Logic algorithms for simulation purposes in order to find the relationship between two fuzzy sets with the computed allocated time.